Cytotoxic Effect of ZnO Nanoparticles on the Viability of Leishmania donovani Promastigotes in vitro - Enad, Ahmed Talal; Zghair, Khawla Hori (Iraqi Journal of Science, 2022)
Leishmaniasis is an endemic disease in Iraq, where both forms of the disease, cutaneous and visceral, are found. The effect of Zinc oxide nanoparticles (ZnO NPs) with mean particle size less than 100 nanometer (nm) on viability and growth rate of Leishmania donovani promastigotes was evaluated. The anti-leishmanial activity of different concentrations (0.1, 0.2, 0.4, 0.6, 0.8, and 1 μg/ml) of ZnO NPs was investigated on promastigotes growth rates and viability in comparison to promastigotes exposed to the same concentrations of sodium stibogluconate (Sb) (pentostam).The inhibitory concentrations (IC50s) of ZnO NPs were calculated after 24 , 48 and 72 hr which were (0.871, 0.156 and 0.120 μg/ml) respectively with significant (p< 0.05) differences between them ,while the IC50 of pentostam cannot calculated because more than 50% of parasites number remained viable after 24 ,48 and 72hr.The IC50s also calculated on the viability results to determine the most effective concentrations. They were 0.434, 0.361 and 0.182 μg/ml for promastigotes exposed to ZnO NPs after 24, 48 and 72hr respectively, while the same concentrations of Sb in the same periods didn't revealed the IC50s. The results concluded that ZnO NPs affect on the growth rate and viability of L. donovani promastigotes by dose and time-depended manner in vitro condition.